2015
DOI: 10.1525/collabra.23
|View full text |Cite
|
Sign up to set email alerts
|

A New Replication Norm for Psychology

Abstract: There is growing consensus that psychology has a replicability "crisis of confidence" [70,69,89,66,67], stemming from the fact that a growing number of findings cannot be replicated via high-powered independent replication attempts that duplicate the original methodology as closely as possible. Across all areas of psychology, there is a growing list of (prominent) findings that have not held up to independent replication attempts, including findings from cognitive psychology (retrieval- [38,17,51,18,31,57,72,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…Again, we need to emphasize that the issue being discussed here does not lie in (internal) meta-analysis per se, but in researchers' (implicit) motivation to use the strategic flexible stopping rule to maximize positive results with NHST (see also, Ioannidis, 2005;Klein et al, 2014;Open Science Collaboration, 2012, 2013, 2015Pashler & Harris, 2012;Pashler & Wagenmakers, 2012). Without using the flexible stopping rule, one can reliably keep false positive error rates to the conventional nominal level (e.g., 5%) regardless of how many studies are integrated within an article.…”
Section: Possible Strategies To Control Type I Error Inflations In In...mentioning
confidence: 99%
See 1 more Smart Citation
“…Again, we need to emphasize that the issue being discussed here does not lie in (internal) meta-analysis per se, but in researchers' (implicit) motivation to use the strategic flexible stopping rule to maximize positive results with NHST (see also, Ioannidis, 2005;Klein et al, 2014;Open Science Collaboration, 2012, 2013, 2015Pashler & Harris, 2012;Pashler & Wagenmakers, 2012). Without using the flexible stopping rule, one can reliably keep false positive error rates to the conventional nominal level (e.g., 5%) regardless of how many studies are integrated within an article.…”
Section: Possible Strategies To Control Type I Error Inflations In In...mentioning
confidence: 99%
“…In fact, a recent large-scale reproducibility project (Open Science Collaboration, 2015) found that the effect sizes in (high-powered) replication studies were half the magnitude of the original effects of 100 articles in high-profile journals from cognitive and social psychology (see also, Klein et al, 2014; Open Science Collaboration, 2012, 2013; Pashler & Harris, 2012; Pashler & Wagenmakers, 2012). LeBel (2015) also argued that this issue is not limited to cognitive and social psychology, but is prevalent in most fields of psychology (or perhaps in other scientific fields, e.g., neuroscience). These findings clearly demonstrate the value of conducting high powered research in psychology to accurately ascertain effect size.…”
mentioning
confidence: 99%
“…In response to the current replication crisis in psychology (for discussions, see Pashler and Wagenmakers, 2012; Maxwell et al, 2015), several solutions have been proposed to improve the quality of psychological research (e.g., Chambers, 2013; Simons, 2014; LeBel, 2015; for overviews, see Ferguson, 2015; Zwaan et al, 2017). Benjamin et al (2018) argue for a change of the standard 0.05 alpha level and instead support to lower the default alpha value for novel findings in the field of psychology to 0.005.…”
Section: Introductionmentioning
confidence: 99%
“…One potential solution to this problem is to make replication an explicit part of pedagogy: that is, to teach students about experimental methods by asking them to run replication studies (Frank & Saxe, 2012; Grahe et al, 2012). Despite enthusiasm for this idea (Everett & Earp, 2015; King et al, 2016; LeBel, 2015; Standing, 2016), there is limited data beyond anecdotal reports and individual projects (e.g., Lakens, 2013; Phillips et al, 2015) to suggest that the pedagogical use of replications should be adopted on a broader scale.…”
mentioning
confidence: 99%